Empowering Pelajar Melalui Pelatihan Kewirausahaan : Pengembangan Pengemasan dan Pelabelan Produk Lossava - Laela Nur Rokhmah; Binardo Adi Seno Mawarno; Jayanti Rahayu; Evida Agustina Sari (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
Students are potential group for fastering entrepreneurial spirit from an early age. However, limited skills in packaging and product labeling pose challenges in developing that potential. This community service activity aimed to enhance student’s entrepreneurial spirit through entrepreneurship training focused on packaging and labeling of Lossava (long cassava), a cassava-based product developed as part of the Pancasila Student Profile Strengthening Project (P5). The methods used were pretest, lecture-based counceling, hands-on practice and posttest. The results showed an increased in partisipants’ understanding, with an average score improvement from 8.0 to 9.5. Students successfully selected functional and attactive packaging designs and created labels in accordance with food labeling production costs and product pricing, with the simulation showing a viable selling proce and significant profit margin. This activity not only provided technical entrepreneurships skills but also instilled values of independence, critical thingking, and creativity in line with the Pancasila student profile. The results indicate that practical based training effectively improves students entrepreneurial competencies and is replicable in other educational settings.   ABSTRAK Pelajar merupakan kelompok potensial dalam membangun kewirausahaan sejak dini. Akan tetapi kurangnya ketrampilan dalam pengemasan dan pelabelan produk menjadi tantangan dalam mengembangkan potensi tersebut. Kegiatan pengabdian ini bertujuan untuk meningkatkan jiwa kewirausahaan pelajar melalui pelatihan kewirausahaan dengan fokus  pada pengemasan dan pelabelan produk Lossava (Long Cassava), produk olahan singkong yang dikembangkan dalam konteks Projek Penguatan Profil Pelajara Pancasila (P5).  Metode kegiatan meliputi pretest, penyuluhan, praktik langsung dan posttest. Hasil menunjukkan peningkatan pemahaman peserta dari skor rata-rata 8,0 menjadi 9,5 setelah pelatihan. Pelajar mampu memilih desain kemasan fungsional dan menarik serta menyusun label sesuai standar informasi pangan. Selain itu, peserta juga dilatih menghitung harga pokok produksi dan harga jual. Simulasi menunjukkan produk layak dijual dengan margin laba yang signifikan. Kegiatan ini tidak hanya membekali pelajar dengan keterampilan teknis kewirausahaan, tetapi juga menanamkan nilai kemandirian, berpikir kritis dan kreatif sesuai profil pelajar Pancasila. Hasil pengabdian menunjukkan bahwa pelatihan berbasis praktik efektif meningkatkan kompetensi kewirausahaan pelajar dan dapat direplikasi dalam konteks pendidikan lainnya.